An Investigation of The Reasons For and Expectations From Boxing Participation of Male Athletes Who Participated in The School Sports Young Adults B Category Boxing Turkey Championship - Hüseyin Çiçek; Metin Yaman (Türk Spor ve Egzersiz Dergisi)
The present study aims to investigate the reasons for and expectations from boxing participation of male athletes who participated in the 2018 School Sports Young Adults B Category Boxing Turkey Championship held in Erzincan.    The present study enrolled the licensed athletes who participated in the 2018 School Sports Young Adults B Category Boxing Turkey Championship. A total of 150 athletes participated in this Championship. It was conducted with the voluntary participation of the male athletes participating in the Turkey Finals of the School Sports Young Adults B Category. The population of the study consists of 150 athletes, and the sample consists of 102 male athletes.  Personal information form developed by Ayilgan (2017) was used to collect the data. The data were analysed by frequency distribution and percentage distribution in SPSS 17.0 package program.   Of the participants, 2% were in the 10-14 age range while 98% were in the 15-19 age range. Besides, 33.3% of the participants reside in metropolises, 51.0% in cities and 15.7% in districts.  It was also found that 31.4% of the  participants  were engaged in boxing for one year, 18.6% for two years, 18.6% for three years, 15.7% for four years, and 15.7% for five years and more.  A majority (52%) of the participants planned to be national athletes in the future and received sufficient support from their social circles. 47% of the participants received rewards or bonuses from their clubs whereas 53% received no awards or bonuses.   Considering the responses of the athletes who participated in our study, it can be seen that they are fond of boxing and their social circles have sufficient knowledge of boxing.